2018
DOI: 10.1155/2018/9174868
|View full text |Cite
|
Sign up to set email alerts
|

Carboxyhaemoglobin Levels among Traders Exposed to Vehicular Emissions in Three Motor Parks in Ibadan, Nigeria

Abstract: Carbon monoxide (CO) remains a leading cause of work-related chemical poisoning. Vehicular emissions are the primary daily ambient source of CO in urban Nigerian motor parks, where there have been few human exposure studies. Using a cross-sectional comparative design, we assessed carboxyhaemoglobin levels (% COHb), a biomarker of CO exposure, among traders at three motor parks (AMP, IMP, and NMP) and other traders (nonmotor park workers) in Ibadan, Nigeria, using a noninvasive pulse CO-dosimeter (Rad 57). Nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…The findings of this study is in line with the work ofOgunseye et al (2018) which reported high CO concentration within motor parks in Ilorin with its associated effects on park works, users and traders.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…The findings of this study is in line with the work ofOgunseye et al (2018) which reported high CO concentration within motor parks in Ilorin with its associated effects on park works, users and traders.…”
supporting
confidence: 91%
“…al., 2020). Traders in motor parks spend about 6 -8 hours daily in those motor parks, hence they are at risk of possible exposure to carbon monoxide arising from vehicles and other emission sources in motor parks (Olusola et. al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…dan akibat paparan materi debu, maka keluhan kesehatan yang disebabkan oleh keracunan gas CO dapat disebabkan oleh agen penyebab lainnya yang mana keluhan-keluhan kesehatannya hampir sama dengan keracunan gas CO (31) .…”
Section: Simpulanunclassified
“…In another study in Ibadan, Nigeria, a cross-sectional comparative study Ref. [ 21 ] found that motor park sellers were more susceptible to carboxyhemoglobin levels (COHb) and are more prone to risks of poor health resulting from CO exposure. The study corroborated that men were less knowledgeable about air pollution than women [ 22 ].…”
Section: Introductionmentioning
confidence: 99%